Analysis Of Added Value And Income Of Robusta Coffee Bean Processing Business Into Coffee Powder In Tanjung Menang Village, Jarai District, Lahat Regency, South Sumatera Province - Sri Rahayu Endang Lestari; Gusti Fitriyana; Davina Athiya Ramadanty (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
This study aims to determine the selling price of robusta coffee beans before being processed into robusta coffee powder, the amount of added value obtained by coffee producers from processing robusta coffee powder, and the amount of income of robusta coffee producers. This study was conducted in Tanjung Menang Village, Jarai District, Lahat Regency, South Sumatra Province. This study was conducted from December 2024 to January 2025. The Hayami method, which applies the calculation of output units and is studied in depth (Indepth Study) in the case of Kopi Petani Kite is the added value analysis used in this study. Based on the analysis that has been carried out on Kopi Petani Kite in one month of production, an added value of IDR 78,400 per kilogram has been obtained while the income obtained was IDR 4,179,500 at the time the study was conducted